Island species radiation and karyotypic stasis in Pachycladon allopolyploids - Mandáková, Terezie; Heenan, Peter B; Lysak, Martin A (BMC evolutionary biology, 2010)
BACKGROUND: Pachycladon (Brassicaceae, tribe Camelineae) is a monophyletic genus of ten morphologically and ecogeographically differentiated, and presumably allopolyploid species occurring in the South Island of New Zealand and in Tasmania. All Pachycladon species possess ten chromosome pairs (2n = 20). The feasibility of comparative chromosome painting (CCP) in crucifer species allows the origin and genome evolution in this genus to be elucidated. We focus on the origin and genome evolution of Pachycladon as well as on its genomic relationship to other crucifer species, particularly to the allopolyploid Australian Camelineae taxa. As species radiation on islands is usually characterized by chromosomal stasis, i.e. uniformity of chromosome numbers/ploidy levels, the role of major karyotypic reshuffling during the island adaptive and species radiation in Pachycladon is investigated through whole-genome CCP analysis. RESULTS: The four analyzed Pachycladon species possess an identical karyotype structure. The consensual ancestral karyotype is most likely common to all Pachycladon species and corroborates the monophyletic origin of the genus evidenced by previous phylogenetic analyses. The ancestral Pachycladon karyotype (n = 10) originated through an allopolyploidization event between two genomes structurally resembling the Ancestral Crucifer Karyotype (ACK, n = 8). The primary allopolyploid (apparently with n = 16) has undergone genome reshuffling by descending dysploidy toward n = 10. Chromosome "fusions" were mediated by inversions, translocations and centromere inactivation/loss. Pachycladon chromosome 3 (PC3) resulted from insertional fusion, described in grasses. The allopolyploid ancestor originated in Australia, from the same or closely related ACK-like parental species as the Australian Camelineae allopolyploids. However, the two whole-genome duplication (WGD) events were independent, with the Pachycladon WGD being significantly younger. The long-distance dispersal of the diploidized Pachycladon ancestor to New Zealand was followed by the Pleistocene species radiation in alpine habitats and characterized by karyotypic stasis. CONCLUSIONS: Karyotypic stasis in Pachycladon suggests that the insular species radiation in this genus proceeded through homoploid divergence rather than through species-specific gross chromosomal repatterning. The ancestral Pachycladon genome originated in Australia through an allopolyploidization event involving two closely related parental genomes, and spread to New Zealand by a long-distance dispersal. We argue that the chromosome number decrease mediated by inter-genomic reshuffling (diploidization) could provide the Pachycladon allopolyploid founder with an adaptive advantage to colonize montane/alpine habitats. The ancestral Pachycladon karyotype remained stable during the Pleistocene adaptive radiation into ten different species.
Keywords: Genetic Speciation; Tasmánie; zeměpis; genom rostlinný; Genome, Plant; karyotypizace; Nový Zéland; fylogeneze; Chromosome Painting; Phylogeny; Karyotyping; biologická evoluce; Brassicaceae; Geography; vznik druhů (genetika); DNA rostlinná; DNA, Plant; Tasmania; Biological Evolution; New Zealand; malování chromozomů